MEMORY AS THE LANGUAGE BOUNDARY OF MODERN EUROPEAN PHILOSOPHY - K. P. Shevtsov (Дискурс)
In this paper we propose to consider the concept of memory in modern philosophy as an essential element of language of the philosophical systems of this period. The main thesis of the article is that, starting with Descartes and up to classical German philosophy, an interest in the problem of memory is directly related to the resolution of internal paradoxes that arise in these systems.